JA:2021-30. Constant Contact ® Readership Analytics: Lessons Learned. Issue 3 (2nd July 2020) - Sauer, Megan; Ploeckelman, Melissa; Pilz, Matthew; Redmond, Emily; Burke, Rick; Koshalek, Kyle; Heiberger, Scott; Weichelt, Bryan
ABSTRACT: Purpose : With the increased adoption of digital communications to disseminate agricultural-related news and information, it is imperative to monitor and tailor the content based on actual user engagement and observed trends. This study assesses information gleaned through analysis of available reporting data – views, click-through rates, mobile access, story popularity – and what limitations exist within the analytics. Subscribers are automatically opted in for the e-Newsletter upon registering for AgInjuryNews.org. We monitor website and newsletter analytics to better understand the interests and behaviors of our users – agricultural safety and health stakeholders – and which topics engage them. Methods : The AgInjuryNews.org e-Newsletter analytics were obtained through the Constant Contact website. We track user information, date, and time of interaction, as well as topics clicked on. We also assess all types of engagement rates of each published issue. We cannot track if users read the content or simply open the email and then close it. The open rate is also difficult to interpret, since certain e-mail servers do not download pictures within the e-Newsletter automatically, so if a subscriber does not manually click to download pictures within the e-mail, the Constant Contact software will not record it as an opened e-mail. Results/Findings : The AgInjuryNews Constant Contact e-Newsletter has been published three times and key findings include: 1) 81–85% of opens are through desktop vs. mobile devices, 2) we have seen a low bounce rate average of 10%, and 3) the topics of interest, based upon user clicks, include AgInjuryNews.org, published peer-reviewed articles, and other farm-related fatality reports and summaries. Practical Application : By presenting our Constant Contact lessons learned, we can share issues found, user behavior data, and what we have identified to be engaging content topics within this communications format. The AgInjuryNews Constant Contact Newsletter helps to keep registered users informed of pertinent initiative updates. Other organizations utilizing Constant Contact to regularly engage customers/members/readers with their content could benefit from what we have learned during this pilot project.